Phospholipase A2 regulation of bovine endometrial (BEND) cell prostaglandin production - Guan Wei; Elgayyar Mona; Roberts Mary P; Godkin James D; Tithof Patricia K (BMC, 2008)
Abstract Background Prostaglandins (PG), produced by the uterine endometrium, are key regulators of several reproductive events, including estrous cyclicity, implantation, pregnancy maintenance and parturition. Phospholipase A2 (PLA2) catalyzes the release of arachidonic acid from membrane phospholipids, the rate-limiting step in PG biosynthesis. The bovine endometrial (BEND) cell line has served as a model system for investigating regulation of signaling mechanisms involved in uterine PG production but information concerning the specific PLA2 enzymes involved and their role in regulation of this process is limited. The objectives of this investigation were to evaluate the expression and activities of calcium-dependent group IVA (PLA2G4A) and calcium-independent group VI (PLA2G6) enzymes in the regulation of BEND cell PG production. Methods Cells were grown to near-confluence and treated with phorbol 12, 13 dibutyrate (PDBu), interferon-tau (IFNT), the PLA2G4A inhibitor pyrrolidine-1 (PYR-1), the PLA2G6 inhibitor bromoenol lactone (BEL) and combinations of each. Concentrations of PGF2alpha and PGE2 released into the medium were determined. Western blot analysis was performed on cellular protein to determine effects of treatment on expression of PLA2G4A, PLA2G6 and PLA2G4C. PLA2 assays were performed on intact cells by measuring arachidonic acid and linoleic acid release and group-specific PLA2 activity assays were performed on cell lysates. Results BEND cells produced about 10-fold more PGE2 than PGF2alpha under resting conditions. Production of both PGs increased significantly in response to PDBu-stimulation. PYR-1 significantly diminished production of both PGs by resting cells and abolished the stimulatory effect of PDBu. BEL stimulated production of both PGs. IFNT reduced both PGE2 and PGF2alpha production by resting cells and diminished PDBu stimulation of PG production. Conversely, IFNT did not significantly reduce BEL stimulation of PG production. Cellular expression of PLA2G4A was enhanced by PDBu and this response was diminished by IFNT. Expression of PLA2G6 was not observed to be affected by treatments and no PLA2G4C expression was observed. Arachidonic acid release from intact cells was significantly increased by PDBu and this effect was attenuated by PYR-1 but not by BEL. Release of linoleic acid from intact cells was stimulated by PDBu and inhibited by BEL but not PYR-1. Group specific PLA2-activity assays demonstrated both PLA2G4A and PLA2G6 activity. Conclusion Results from this study demonstrate that PGE2 and PGF2-alpha production by BEND cells is mediated by the activity and expression of PLA2G4A. Interferon-tau treatment diminished expression of PLA2G4A and PG production. BEND cells were shown to express PLA2G6 but, unlike primary or early passage luminal bovine endometrial cells, stimulation of PLA2G6 activity was not associated with increased PG production.